Air pollution induces pyroptosis of human monocytes through activation of inflammasomes and Caspase-3-dependent pathways - Adrianna Gałuszka-Bulaga; Karolina Tkacz; Kazimierz Węglarczyk; Maciej Siedlar; Jarek Baran (BMC, 2023)
Abstract According to the World Health Organization (WHO), air pollution is one of the most serious threats for our planet. Despite a growing public awareness of the harmful effects of air pollution on human health, the specific influence of particulate matter (PM) on human immune cells remains poorly understood. In this study, we investigated the effect of PM on peripheral blood monocytes in vitro. Monocytes from healthy donors (HD) were exposed to two types of PM: NIST (SRM 1648a, standard urban particulate matter from the US National Institute for Standards and Technology) and LAP (SRM 1648a with the organic fraction removed). The exposure to PM-induced mitochondrial ROS production followed by the decrease of mitochondrial membrane potential and activation of apoptotic protease activating factor 1 (Apaf-1), Caspase-9, and Caspase-3, leading to the cleavage of Gasdermin E (GSDME), and initiation of pyroptosis. Further analysis showed a simultaneous PM-dependent activation of inflammasomes, including NLRP3 (nucleotide-binding oligomerization domain-like receptor pyrin domain containing 3) and Caspase-1, followed by cleavage of Gasdermin D (GSDMD) and secretion of IL-1β. These observations suggest that PM-treated monocytes die by pyroptosis activated by two parallel signaling pathways, related to the inorganic and organic PM components. The release of IL-1β and expression of danger-associated molecular patterns (DAMPs) by pyroptotic cells further activated the remnant viable monocytes to produce inflammatory cytokines (TNF-α, IL-6, IL-8) and protected them from death induced by the second challenge with PM. In summary, our report shows that PM exposure significantly impacts monocyte function and induces their death by pyroptosis. Our observations indicate that the composition of PM plays a crucial role in this process-the inorganic fraction of PM is responsible for the induction of the Caspase-3-dependent pyroptotic pathway. At the same time, the canonical inflammasome path is activated by the organic components of PM, including LPS (Lipopolysaccharide/endotoxin). Graphical Abstract PM-induced pyroptosis of human monocytes. Particulate matter (PM) treatment affects monocytes viability already after 15 min of their exposure to NIST or LAP in vitro. The remnant viable monocytes in response to danger-associated molecular patterns (DAMPs) release pro-inflammatory cytokines and activate Th1 and Th17 cells. The mechanism of PM-induced cell death includes the increase of reactive oxygen species (ROS) production followed by collapse of mitochondrial membrane potential (ΔΨm), activation of Apaf-1, Caspase-9 and Caspase-3, leading to activation of Caspase-3-dependent pyroptotic pathway, where Caspase-3 cleaves Gasdermin E (GSDME) to produce a N-terminal fragment responsible for the switch from apoptosis to pyroptosis. At the same time, PM activates the canonical inflammasome pathway, where activated Caspase-1 cleaves the cytosolic Gasdermin D (GSDMD) to produce N-terminal domain allowing IL-1β secretion. As a result, PM-treated monocytes die by pyroptosis activated by two parallel pathways-Caspase-3-dependent pathway related to the inorganic fraction of PM and the canonical inflammasome pathway dependent on the organic components of PM.